1996
DOI: 10.1021/la960271g
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of 6-O-Stearoylascorbic Acid and Vitamin K1 in Mixed Langmuir Films at the Gas/Water Interface

Abstract: 6-O-Stearoylascorbic acid (ASC) and vitamin K1 (2-methyl-3-phytylnaphthoquinone) behave as surfactant molecules and form stable monomolecular spreading films at the gas/water interface. This paper reports an investigation on the miscibility of these two amphiphiles in monolayers as a function of temperature and composition of the mixture. A thermodynamic theory is applied to the experimental results in order to obtain information on the intermolecular interactions occurring at the gas/water interface between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…The addition of ASC 12 to ocular topical preparation improves the permeation of the hydrophobic drug acetazolamide, more efficiently than ASC 16 [5]. The same picture was observed for permeation of ibuprofen through the mouse skin [6].…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…The addition of ASC 12 to ocular topical preparation improves the permeation of the hydrophobic drug acetazolamide, more efficiently than ASC 16 [5]. The same picture was observed for permeation of ibuprofen through the mouse skin [6].…”
Section: Introductionmentioning
confidence: 54%
“…It has been shown that ASC n conserve part of the radical scavenging activity in aggregates such as micelles. For example, ASC 10 micelles retain about half of the antioxidant performance for oxygen uptake [1], whilst ASC 12 and ASC 14 only retain $40 and $34% of the antioxidant activity [7,9] compared to unmodified L-ascorbic acid. It is well known that L-ascorbic acid is stable in solid form, but it is susceptible to oxidation when in solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cappuzzi et al [129] studied the mixtures of stearoyl ascorbic acid and vitamin K 1 . These two compounds form stable Langmuir films at the air/water interface for temperatures ranging from 20 to 35 • C and are completely miscible in the monolayer in all ratios.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…In the literature, many papers demonstrate the synergic effects between different constituents of Hypericum perforatum L. (Butterweck et al, 1998;Noldner and Schotz, 2002;solubility of the constituents of the extract within the formulations was evaluated to better elucidate the results obtained from the pharmacological tests. (Capuzzi et al, 1996); water content and purity were checked by elemental analysis (theoretical C 55.62%, H 7.33%; found C 53.80%, H 7.45%). Ethanol was analytical reagent grade from Riedelde Haen (Seelze, Germany).…”
Section: Introductionmentioning
confidence: 99%